A highly conductive Na3V2(PO4)3 ceramic sheet prepared by tape-casting method. (10th May 2019) - Wang, He; Hasegawa, George; Akiyama, Yuto; Yamamoto, Takahisa; Inoishi, Atsushi; Akamatsu, Hirofumi; Inada, Miki; Ishihara, Tatsumi; Hayashi, Katsuro
Abstract: Ceramic sheets of Na3 V2 (PO4 )3 (NVP) with NASICON-related structure have been prepared by tape-casting method. The addition of 60Na2 O-10Nb2 O5 -30P2 O5 glass to NVP is demonstrated to enhance markedly the density of the sintered NVP sheet and its electrical conductivity. The best densified NVP sheet with a thickness of a few tens of μm is obtained by sintering tape-casted NVP added with 5 wt% glass at 920 °C, which exhibits a total conductivity of 2.9 × 10 −5  S cm −1  at room temperature. A Pt | NVP sheet | Pt cell works as a tiny solid-state battery with a cell potential of 1.7 V, in which NVP acts as both cathode and anode active materials via redox reactions of V 4+ /V 3+ and V 3+ /V 2+ as well as a Na + ion conducting electrolyte between the two electrode layers.